HUBUNGAN PERAN TENAGA DAN MOTIVASI TERHADAP KELENGKAPAN IMUNISASI TETANUS TOKSOID PADA IBU HAMIL - Minarti, Minarti; Chandra, Tiara Ayu; Riani, Lita (JOURNAL OF HEALTH SCIENCE, 2021)
Tetanus Toxoid (TT) immunization is a process to build immunity as an effort to prevent tetanus infection (Indanati, 2015). The tetanus vaccine is a toxin from the tetanus germ that has been weakened and then purified. The immunity that is transmitted from mother to baby can be a protection for babies against stressors (unsterile delivery and unclean umbilical cord care) that can cause TN. This research is a quantitative research with an analytical survey with a cross sectional approach. The population in this study were all pregnant women who visited totaling 36 pregnant women. The sample of this research used systematic random sampling method. The sample of this study amounted to 36 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of the bivariate analysis showed that there was a relationship between the role of health workers (p value = 0.022) and there was a relationship between motivation (p value = 0.040) and the completeness of tetanus toxoid (TT) immunization for pregnant women. The advice given is expected to be a source of information, input and improve the quality of services, especially regarding TT immunization for pregnant women. Keywords: Completeness of Tetanus Toxoid Immunization for Pregnant Women